2005
DOI: 10.1017/s0003055405051762
|View full text |Cite
|
Sign up to set email alerts
|

Nested Analysis as a Mixed-Method Strategy for Comparative Research

Abstract: D espite repeated calls for the use of "mixed methods" in comparative analysis, political scientists have few systematic guides for carrying out such work. This paper details a unified approach which joins intensive case-study analysis with statistical analysis. Not only are the advantages of each approach combined, but also there is a synergistic value to the nested research design: for example, statistical analyses can guide case selection for in-depth research, provide direction for more focused case studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
506
1
22

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 838 publications
(551 citation statements)
references
References 30 publications
1
506
1
22
Order By: Relevance
“…Our quantitative model below predicts an EU-South Africa PTA particlarly well, so the case is useful for illustrating our theory (Lieberman 2005;Seawright and Gerring 2008). It features a prominent leader change, namely Nelson Mandela's becoming the country's President, at the time of democratization as the black majority gained suffrage.…”
Section: Case Study: South Africamentioning
confidence: 88%
“…Our quantitative model below predicts an EU-South Africa PTA particlarly well, so the case is useful for illustrating our theory (Lieberman 2005;Seawright and Gerring 2008). It features a prominent leader change, namely Nelson Mandela's becoming the country's President, at the time of democratization as the black majority gained suffrage.…”
Section: Case Study: South Africamentioning
confidence: 88%
“…A promising line of enquiry is to use mixed methods (that is, to combine, within the same research project or programme, qualitative and quantitative approaches in order to generate synergies), like in Lieberman's proposal for 'nested analysis'. 59 However, it should be observed that the use of mixed methods necessitates the use of research projects of a minimum scale, possibly going beyond the average scale of individual (comparative) research endeavours.…”
Section: The Problem Of Empirical Methodologymentioning
confidence: 99%
“…To test our hypotheses we apply a nested mixed-method research design (Lieberman 2005). We first assess our arguments using statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For a deeper assessment of our causal argument we undertake a 'model testing' case analysis (Lieberman 2005). We focus on civilian defense forces in Anbar province, Iraq (2005Iraq ( -2009.…”
Section: Case Analysis: Iraqmentioning
confidence: 99%